Cyclic complex or its crystal, rubber composition containing cyclic complex or its crystal, and cured product thereof

JP2025034256APending Publication Date: 2025-03-13SUMITOMO RUBBER INDUSTRIES LTD +1
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
JP2023140538
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-08-30
Publication Date
2025-03-13

AI Technical Summary

Benefits of technology

【0015】 本発明によれば、炭素-炭素不飽和結合を有する新規な環状錯体またはその結晶を提供することができる。また、前記環状錯体またはその結晶を含有するゴム組成物の硬化物は、良好な機械的物性を与える。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025034256000001_ABST
    Figure 2025034256000001_ABST
Patent Text Reader

Abstract

To provide a novel complex having a carbon-carbon unsaturated bond.SOLUTION: A cyclic complex of the present invention has a constituent unit represented by formula (1) as a unit constituting a cyclic structure. [In the formula (1), M1 and M2 are the same or different metal atoms; R1-R4 are each independently a hydrogen atom, an alkyl group, an alkenyl group or an alkynyl group; and at least one of R1-R4 is an alkenyl group or an alkynyl group.]SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a cyclic complex having a carbon-carbon unsaturated bond or a crystal thereof, a rubber composition containing the cyclic complex or the crystal thereof, and a cured product of the rubber composition. [Background technology]

[0002] A rubber composition in which zinc (meth)acrylate is blended with base rubber as a co-crosslinking agent is widely used. The co-crosslinking agent crosslinks the base rubber and improves the physical properties of the resulting cured product. Research and development of new co-crosslinking agents is being conducted to improve the physical properties of the cured rubber. Zinc (meth)acrylate, which is used as a co-crosslinking agent, is known to form various complexes.

[0003] For example, Patent Document 1 discloses a complex represented by structural formula (20).

[0004] [ka]

[0005] [In structural formula (20), M 1 ~M 4 are the same or different metal atoms, and R 1 ~R 6 are the same or different and each represents a hydrogen atom, an alkyl group having 1 to 18 carbon atoms, an alkenyl group having 2 to 18 carbon atoms, or an alkynyl group having 2 to 18 carbon atoms. R 1 ~R 6 At least two of the groups are alkenyl groups having 2 to 18 carbon atoms or alkynyl groups having 2 to 18 carbon atoms.]

[0006] Patent Document 2 discloses a complex represented by formula (21). ((RCOO)8M5(OH)2) n (twenty one) [In formula (21), M is a metal atom, and R is a hydrogen atom, an alkyl group having 1 to 18 carbon atoms, an alkenyl group having 2 to 18 carbon atoms, or an alkynyl group having 2 to 18 carbon atoms. Multiple Rs may be the same or different, provided that at least one of Rs is an alkenyl group having 2 to 18 carbon atoms or an alkynyl group having 2 to 18 carbon atoms. n is an integer of 1 or greater.]

[0007] Patent Document 3 discloses a complex represented by formula (22). [M4O(RCOO)6] n (twenty two) [In formula (22), M is a metal atom, and R is a hydrogen atom, an alkyl group having 1 to 24 carbon atoms, an alkenyl group having 2 to 18 carbon atoms, or an alkynyl group having 2 to 18 carbon atoms. In formula (1), multiple R may be the same or different, provided that at least two of R are alkenyl groups having 2 to 18 carbon atoms, or alkynyl groups having 2 to 18 carbon atoms, and at least one of R is an alkyl group having 6 to 24 carbon atoms. n is an integer of 1 to 8.]

[0008] Patent Document 4 discloses a complex represented by formula (24). [M4O(RCOO)6] n (twenty four) [In formula (1), M is a metal atom, and R is a hydrogen atom, an alkyl group having 1 to 18 carbon atoms, an alkenyl group having 2 to 18 carbon atoms, an alkynyl group having 2 to 18 carbon atoms, or a monovalent group represented by structural formula (25). In formula (24), multiple R may be the same or different. n is an integer of 1 to 8, with the proviso that at least one of R is an alkenyl group having 2 to 18 carbon atoms or an alkynyl group having 2 to 18 carbon atoms, and at least one of R is a monovalent group represented by structural formula (25).

[0009] [ka]

[0010] In structural formula (25), A1 ~A 4 Each of X independently represents a nitrogen atom or a carbon atom. 1 R represents a single bond or a divalent organic group. 1 represents a hydrogen atom or a monovalent organic group. 1 ~A 4 has at least one carbon atom, and X 1 and R 1 is bonded to a carbon atom. n is an integer of 0 to 3. A 1 ~A 4 If one of A is a carbon atom, n is 0. 1 ~A 4 If two of the are carbon atoms, n is 1. 1 ~A 4 If three of the are carbon atoms, n is 2. 1 ~A 4 When all are carbon atoms, n is 3. When n is 2 or more, multiple R 1 may be bonded to each other to form a ring structure. [Prior art documents] [Patent documents]

[0011] [Patent Document 1] JP 2018-104306 A [Patent Document 2] JP 2018-104405 A [Patent Document 3] JP 2020-002020 A [Patent Document 4] JP 2020-002021 A Summary of the Invention [Problem to be solved by the invention]

[0012] An object of the present invention is to provide a novel cyclic complex having a carbon-carbon unsaturated bond or a crystal thereof. Another object of the present invention is to provide a rubber composition containing the cyclic complex or a crystal thereof, and a cured product thereof. [Means for solving the problem]

[0013] The cyclic complex of the present invention is characterized in that it has a structural unit represented by formula (1) as a structural unit constituting a cyclic structure. [ka] [In formula (1), M 1 and M. 2 are the same or different metal atoms, and R 1 ~R 4 are the same or different and each represents a hydrogen atom, an alkyl group having 1 to 18 carbon atoms, an alkenyl group having 2 to 18 carbon atoms, or an alkynyl group having 2 to 18 carbon atoms. R 1 ~R 4 At least one of these is an alkenyl group having 2 to 18 carbon atoms or an alkynyl group having 2 to 18 carbon atoms.] The present invention includes a crystal of the cyclic complex.

[0014] The rubber composition of the present invention comprises (a) a base rubber, (b) a co-crosslinking agent, and (c) a crosslinking initiator, and (b) the co-crosslinking agent contains the cyclic complex of the present invention or a crystal thereof. The present invention also includes a cured product of the rubber composition. Effect of the Invention

[0015] According to the present invention, it is possible to provide a novel cyclic complex having a carbon-carbon unsaturated bond or a crystal thereof. Furthermore, a cured product of a rubber composition containing the cyclic complex or the crystal thereof exhibits good mechanical properties. [Brief description of the drawings]

[0016] [Figure 1] FIG. 2 is a diagram showing an ESI-MS spectrum of the cyclic complex obtained in Example 2. [Diagram 2] FIG. 1 is a diagram showing the 1H-NMR spectrum of the cyclic complex obtained in Example 2. [Diagram 3] FIG. 1 shows the 13C-NMR spectrum of the cyclic complex obtained in Example 2. [Figure 4] FIG. 2 is a diagram showing the X-ray diffraction spectrum of the cyclic complex obtained in Example Production Example 2. [Diagram 5] FIG. 1 shows an X-ray diffraction spectrum of commercially available zinc methacrylate. [Figure 6] 1 is a diagram showing the structure of the cyclic complex obtained in Example 2, determined by single crystal X-ray structure analysis, in which tetrahydrofuran is on the three-fold rotational symmetry axis of the crystal solvent at the center of the ring. [Figure 7] FIG. 2 shows the structure corresponding to that of commercially available zinc methacrylate obtained in Comparative Production Example 1, as determined by single crystal X-ray structure analysis. [Figure 8] FIG. 1 shows the results of comparing the stress-strain curves of a crosslinked rubber molded body using the cyclic complex obtained in Example 2 and a crosslinked rubber molded body using a conventional co-crosslinking agent (amount of cyclic complex or conventional co-crosslinking agent: 30 parts by mass per 100 parts by mass of base rubber). [Figure 9] FIG. 1 shows the results of comparing the stress-strain curves of a crosslinked rubber molded body using the cyclic complex obtained in Example 2 and a crosslinked rubber molded body using a conventional co-crosslinking agent (amount of cyclic complex or conventional co-crosslinking agent: 33 parts by mass per 100 parts by mass of base rubber). [Figure 10] FIG. 2 is a diagram showing the structure of the cyclic complex obtained in Example 1, determined by single crystal X-ray structure analysis. [Figure 11] FIG. 2 is a diagram showing the X-ray diffraction spectrum of the linear zinc methacrylate crystal obtained in Comparative Production Example 1, predicted as a result of single crystal X-ray structure analysis. [Figure 12] FIG. 2 is a diagram showing the X-ray diffraction spectrum of the powder obtained in Example 3. [Figure 13] FIG. 2 is a diagram showing the X-ray diffraction spectrum of the powder obtained in Example 4. [Figure 14] FIG. 1 is a diagram showing the X-ray diffraction spectrum of the powder obtained in Example Production Example 5. [Figure 15] FIG. 2 is a diagram showing the X-ray diffraction spectrum of the powder obtained in Example 6. [Figure 16] FIG. 1 is a diagram showing the X-ray diffraction spectrum of the powder obtained in Example 7. [Figure 17] FIG. 2 is a diagram showing the X-ray diffraction spectrum of the powder obtained in Comparative Production Example 2. [Figure 18] FIG. 2 is a diagram showing the X-ray diffraction spectrum of the powder obtained in Comparative Production Example 3. [Figure 19] FIG. 2 is a diagram showing the X-ray diffraction spectrum of the powder obtained in Comparative Production Example 4. [Figure 20] FIG. 1 shows the X-ray diffraction spectrum of the powder obtained in Comparative Production Example 5. [Figure 21] FIG. 2 is a diagram showing the X-ray diffraction spectrum of the powder obtained in Comparative Production Example 6. [Figure 22] FIG. 1 shows the X-ray diffraction spectrum of the powder obtained in Comparative Production Example 7. [Diagram 23] FIG. 1 shows the X-ray diffraction spectrum of the powder obtained in Comparative Production Example 8. [Figure 24] SEM photographs (a: 50x, b: 500x) of a cross-linked rubber molding of rubber composition No. 5 prepared using commercially available zinc methacrylate. [Diagram 25] SEM photographs (a: 50x, b: 500x) of a cross-linked rubber molding of rubber composition No. 6 produced using commercially available zinc methacrylate. [Figure 26] 4 is a SEM photograph (a: 50x, b: 500x) of a crosslinked rubber molding of rubber composition No. 7 prepared using the cyclic complex obtained in Example Production Example 2. [Figure 27] 4 is a STEM photograph (a: 50x, b: 500x) of a crosslinked rubber molding of rubber composition No. 8 prepared using the cyclic complex obtained in Example Production Example 2. [Figure 28] STEM photographs of cross-linked rubber moldings of rubber composition No. 5, which was made using commercially available zinc methacrylate (a: 20,000x, b: 200,000x, c: 1,000,000x). [Figure 29] STEM photographs of cross-linked rubber moldings of rubber composition No. 6, which was made using commercially available zinc methacrylate (a: 20,000x, b: 200,000x, c: 1,000,000x). [Diagram 30]Photographs of cross-linked rubber moldings of rubber composition No. 7 produced using the cyclic complex obtained in Example Production Example 2 (a: 20,000x, b: 200,000x, c: 1,000,000x). [Diagram 31] Photographs of cross-linked rubber moldings of rubber composition No. 8 produced using the cyclic complex obtained in Example Production Example 2 (a: 20,000x, b: 200,000x, c: 1,000,000x). [Diagram 32] FIG. 2 is an explanatory diagram illustrating the crystal structure of a cyclic complex of the present invention. [Diagram 33] FIG. 2 is an explanatory diagram illustrating the crystal structure of a cyclic complex of the present invention. [Diagram 34] FIG. 2 is an explanatory diagram illustrating the crystal structure of a cyclic complex of the present invention. [Diagram 35] FIG. 2 is an explanatory diagram illustrating the crystal structure of a cyclic complex of the present invention. [Diagram 36] FIG. 2 is an explanatory diagram illustrating the crystal structure of a cyclic complex of the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0017] The cyclic complex of the present invention is characterized in that it has a structural unit represented by formula (1) as a structural unit constituting a cyclic structure.

[0018] [ka] [In formula (1), M 1 and M. 2 are the same or different metal atoms, and R 1 ~R 4 are the same or different and each represents a hydrogen atom, an alkyl group having 1 to 18 carbon atoms, an alkenyl group having 2 to 18 carbon atoms, or an alkynyl group having 2 to 18 carbon atoms. R 1 ~R 4 At least one of these is an alkenyl group having 2 to 18 carbon atoms or an alkynyl group having 2 to 18 carbon atoms.]

[0019] The cyclic complex of the present invention having a structural unit represented by formula (1) as a structural unit constituting a cyclic structure has, for example, a structure represented by formula (2).

[0020] [ka]

[0021] [In formula (2), M 1 and M. 2 are the same or different metal atoms, and R 1 ~R 4 are the same or different and each represents a hydrogen atom, an alkyl group having 1 to 18 carbon atoms, an alkenyl group having 2 to 18 carbon atoms, or an alkynyl group having 2 to 18 carbon atoms. R 1 ~R 4 At least one of the groups is an alkenyl group having 2 to 18 carbon atoms or an alkynyl group having 2 to 18 carbon atoms. n is an integer of 3 or more.]

[0022] A complex is a molecular compound in which an atom or an atomic group called a ligand is bonded to a metal atom or a metal ion, and is also called a coordination compound. In the present invention, a cyclic complex is a compound in which adjacent structural units of the cyclic complex are bonded to each other by a bond M. 2 This refers to a complex in which a ring structure is formed by bonding via -O.

[0023] In formula (1) and formula (2), the dashed lines on the solid lines indicate that the carbonyl bond (-C=O) of the carboxylate group and the single bond (-CO-) are in resonance hybridization. In formula (1), both the covalent bond and the coordinate bond are shown with solid lines.

[0024] The cyclic complex represented by formula (2) is a complex having a cyclic structure formed by bonding n constitutional units represented by formula (1). From the viewpoint of easiness of obtaining a cyclic structure, the n is preferably 3 or more, more preferably 4 or more, and even more preferably 5 or more. The upper limit of the n is not particularly limited, but is preferably 50 or less, more preferably 20 or less, even more preferably 10 or less, and particularly preferably 6.

[0025] The structural units of the cyclic complexes represented by formula (1) and formula (2) each have four carboxylate groups (R1 COO, R 2 COO, R 3 COO, R 4 COO) and two metal atoms M 1 , M 2 It consists of three carboxylate groups (R 1 COO, R 2 COO, R 3 COO) is a metal atom M present in the same structural unit. 1 , M 2 Coordinates to one carboxylate group (R 4 Of the oxygen atoms in the COO), one oxygen atom is connected to a metal atom M present in the same structural unit. 1 The other oxygen atom is coordinated to a metal atom M 2 In this way, the adjacent structural units of the complex are coordinated to each other through coordinate bonds M 2 The bond is made via -O to form a ring structure.

[0026] In formula (1) and formula (2), M 1 and M. 2 Examples of the metal atom represented by the formula (I) include alkali metals such as lithium, sodium, potassium, rubidium, and cesium; alkaline earth metals such as calcium, strontium, and barium; transition metals such as scandium, titanium, vanadium, chromium, manganese, iron, cobalt, nickel, copper, yttrium, zirconium, niobium, molybdenum, technetium, ruthenium, rhodium, palladium, silver, hafnium, tantalum, tungsten, rhenium, osmium, iridium, platinum, and gold; and base metals such as beryllium, magnesium, aluminum, zinc, gallium, cadmium, indium, tin, thallium, lead, bismuth, and polonium. Among these, the metal atom M 1 and M. 2 is preferably a metal atom having an oxidation number of +2, more preferably at least one metal atom selected from the group consisting of zinc, beryllium, lead, magnesium, nickel and copper, and even more preferably zinc.

[0027] In one of the structural units of the formula (1) and the formula (2), the metal atom M 1 and M. 2 may be different, but are preferably the same metal atom.

[0028] In formula (1) and formula (2), R 1 ~R 4 Examples of the alkyl group having 1 to 18 carbon atoms include a methyl group, an ethyl group, a propyl group, a butyl group, a pentyl group, a hexyl group, a heptyl group, an octyl group, a nonyl group, a decyl group, an undecyl group, a dodecyl group, a tridecyl group, a tetradecyl group, a pentadecyl group, a hexadecyl group, a heptadecyl group, and an octadecyl group. The alkyl group may be linear, branched, or cyclic.

[0029] The alkyl group preferably has 1 or more carbon atoms, more preferably 2 or more, and even more preferably 3 or more carbon atoms; and preferably has 18 or less, more preferably 15 or less, even more preferably 10 or less, and particularly preferably 8 or less carbon atoms.

[0030] The alkyl group is preferably an ethyl group, a propyl group, or a butyl group.

[0031] In formula (1) and formula (2), R 1 ~R 4 Examples of the alkenyl group having 2 to 18 carbon atoms include an ethenyl group (vinyl group), a 1-propenyl group, a 2-propenyl group, an isopropenyl group, a butenyl group, a pentenyl group, a hexenyl group, a heptenyl group, an octenyl group, a nonenyl group, a decenyl group, an undecenyl group, a dodecenyl group, a tridecenyl group, a tetradecenyl group, a pentadecenyl group, a hexadecenyl group, a heptadecenyl group, and an octadecenyl group. The alkenyl group may be either linear or branched.

[0032] The alkenyl group preferably has one carbon-carbon double bond, and the position of the double bond is preferably the α, β position or the carbon-carbon double bond is preferably at the terminal of the alkenyl group.

[0033] The alkenyl group preferably has 2 or more carbon atoms, more preferably 3 or more carbon atoms, and preferably has 18 or less, more preferably 10 or less, even more preferably 8 or less, and particularly preferably 6 or less carbon atoms.

[0034] The alkenyl group is preferably a vinyl group, an isopropenyl group, a 1-propenyl group, or a 2-propenyl group.

[0035] In formula (1) and formula (2), R 1 ~R 4 Examples of the alkynyl group having 2 to 18 carbon atoms include an ethynyl group, a 1-propynyl group, a 2-propynyl group, a butynyl group, a pentynyl group, a hexynyl group, a heptynyl group, an octynyl group, a nonynyl group, a decynyl group, an undecynyl group, a dodecynyl group, a tridecynyl group, a tetradecynyl group, a pentadecynyl group, a hexadecynyl group, a heptadecynyl group, a heptadecynyl group, and an octadecynyl group. The alkynyl group may be either linear or branched.

[0036] The alkynyl group preferably has one carbon-carbon triple bond, and the carbon-carbon triple bond is preferably located at the α, β position or at the terminal of the alkynyl group.

[0037] The alkynyl group preferably has 2 or more, more preferably 3 or more, and preferably has 18 or less, more preferably 10 or less, further preferably 8 or less, and particularly preferably 6 or less.

[0038] The alkynyl group is preferably an ethynyl group, a 1-propynyl group, or a 2-propynyl group.

[0039] In formula (1) and formula (2), R1 ~R 4 At least one of the R is an alkenyl group having 2 to 18 carbon atoms or an alkynyl group having 2 to 18 carbon atoms. 1 ~R 4 The number of alkenyl groups having 2 to 18 carbon atoms or alkynyl groups having 2 to 18 carbon atoms in the alkyl group is preferably 2 or more, more preferably 3 or more, and most preferably 4.

[0040] In formula (1) and formula (2), R 1 ~R 4 Among these, at least one (preferably at least two, more preferably at least three, and most preferably four) is preferably an alkenyl group having 2 to 8 carbon atoms or an alkynyl group having 2 to 8 carbon atoms, more preferably an alkenyl group having 2 to 8 carbon atoms and a terminal carbon-carbon double bond or an alkynyl group having 2 to 8 carbon atoms and a terminal carbon-carbon triple bond, and further preferably a vinyl group or an isopropenyl group.

[0041] In one of the constitutional units of formula (1) and formula (2), R 1 ~R 4 may be the same or different, but is preferably the same.

[0042] The cyclic complex represented by formula (2) has a plurality of constitutional units represented by formula (1). The plurality of constitutional units (1) each independently contain a different metal atom M 1 and M. 2 and the same metal atom M 1 and M. 2 In a more preferred embodiment of the present invention, all of the structural units (1) constituting the cyclic structure may have the same metal atom M 1 and M. 2 has.

[0043] The cyclic complex represented by formula (2) has a plurality of constitutional units represented by formula (1). The plurality of constitutional units (1) each independently have different R 1 ~R 4or the same R 1 ~R 4 In a more preferred embodiment of the present invention, all of the structural units (1) constituting the cyclic structure may have the same R 1 ~R 4 has.

[0044] In the most preferred embodiment of the present invention, the cyclic complexes represented by formula (1) and formula (2) include, for example, R 1 ~R 4 is a vinyl group (-CH=CH2), and the metal atom M 1 , M 2 R is a complex where R is zinc (Zn); 1 ~R 4 is an isopropenyl group (-C(CH3)=CH2), and the metal atom M 1 , M 2 is zinc (Zn).

[0045] The cyclic complex of the present invention can be produced using a compound represented by the following formula (3) (hereinafter, sometimes simply referred to as "compound (3)"). [M(RCOO) x ]·yH2O···(3) [In formula (3), M is a metal atom, and R is a hydrogen atom, an alkyl group having 1 to 18 carbon atoms, an alkenyl group having 2 to 18 carbon atoms, or an alkynyl group having 2 to 18 carbon atoms. x is a number corresponding to the oxidation number of the metal atom M and is an integer of 1 or more. y is an integer of 0 or more. A plurality of R's may be the same or different.]

[0046] Examples of the metal atom (M) in formula (3) include alkali metals such as lithium, sodium, potassium, rubidium, and cesium; alkaline earth metals such as calcium, strontium, and barium; transition metals such as scandium, titanium, vanadium, chromium, manganese, iron, cobalt, nickel, copper, yttrium, zirconium, niobium, molybdenum, technetium, ruthenium, rhodium, palladium, silver, hafnium, tantalum, tungsten, rhenium, osmium, iridium, platinum, and gold; and base metals such as beryllium, magnesium, aluminum, zinc, gallium, cadmium, indium, tin, thallium, lead, bismuth, and polonium. Among these, the metal atom (M) is preferably a metal atom capable of forming a divalent metal ion, more preferably at least one selected from the group consisting of zinc, beryllium, lead, magnesium, nickel, and copper, and even more preferably zinc.

[0047] R in compound (3) is a hydrogen atom, an alkyl group having 1 to 18 carbon atoms, an alkenyl group having 2 to 18 carbon atoms, or an alkynyl group having 2 to 18 carbon atoms.

[0048] Examples of the alkyl group having 1 to 18 carbon atoms include a methyl group, an ethyl group, a propyl group, a butyl group, a pentyl group, a hexyl group, a heptyl group, an octyl group, a nonyl group, a decyl group, an undecyl group, a dodecyl group, a tridecyl group, a tetradecyl group, a pentadecyl group, a hexadecyl group, a heptadecyl group, and an octadecyl group. The alkyl group may be linear, branched, or cyclic.

[0049] The alkyl group preferably has 1 or more carbon atoms, more preferably 2 or more, and even more preferably 3 or more carbon atoms; and preferably has 18 or less, more preferably 15 or less, even more preferably 10 or less, and particularly preferably 8 or less carbon atoms.

[0050] The alkyl group is preferably an ethyl group, a propyl group, or a butyl group.

[0051] Examples of the alkenyl group having 2 to 18 carbon atoms include ethenyl group (vinyl group), 1-propenyl group, 2-propenyl group, isopropenyl group, butenyl group, pentenyl group, hexenyl group, heptenyl group, octenyl group, nonenyl group, decenyl group, undecenyl group, dodecenyl group, tridecenyl group, tetradecenyl group, pentadecenyl group, hexadecenyl group, heptadecenyl group, and octadecenyl group. The alkenyl group may be either linear or branched.

[0052] The alkenyl group preferably has one carbon-carbon double bond, and the position of the double bond is preferably the α, β position or the carbon-carbon double bond is preferably at the terminal of the alkenyl group.

[0053] The alkenyl group preferably has 2 or more carbon atoms, more preferably 3 or more carbon atoms, and preferably has 18 or less, more preferably 10 or less, even more preferably 8 or less, and particularly preferably 6 or less carbon atoms.

[0054] The alkenyl group is preferably a vinyl group, an isopropenyl group, a 1-propenyl group, or a 2-propenyl group.

[0055] Examples of the alkynyl group having 2 to 18 carbon atoms include an ethynyl group, a 1-propynyl group, a 2-propynyl group, a butynyl group, a pentynyl group, a hexynyl group, a heptynyl group, an octynyl group, a nonynyl group, a decynyl group, an undecynyl group, a dodecynyl group, a tridecynyl group, a tetradecynyl group, a pentadecynyl group, a hexadecynyl group, a heptadecynyl group, a heptadecynyl group, an octadecynyl group, etc. The alkynyl group may be either linear or branched.

[0056] The alkynyl group preferably has one carbon-carbon triple bond, and the carbon-carbon triple bond is preferably located at the α, β position or at the terminal of the alkynyl group.

[0057] The alkynyl group preferably has 2 or more, more preferably 3 or more, and preferably has 18 or less, more preferably 10 or less, further preferably 8 or less, and particularly preferably 6 or less.

[0058] The alkynyl group is preferably an ethynyl group, a 1-propynyl group, or a 2-propynyl group.

[0059] x represents the number of carboxylate groups (RCOO) in compound (3). x is a number corresponding to the oxidation number of metal atom M and is an integer of 1 or more. x is, for example, preferably 1 to 5, and more preferably 2 to 3. y is an integer of 0 or more. y is, for example, preferably 0 to 5, and more preferably 0 to 1.

[0060] Specific examples of compound (3) include fatty acid metal salts of formula (3) where y = 0, and hydrates of fatty acid metal salts of formula (3) where y ≥ 1. Fatty acids constituting the fatty acid metal salts include saturated fatty acids having 1 to 19 carbon atoms, and unsaturated fatty acids having 3 to 19 carbon atoms.

[0061] Examples of the saturated fatty acid include methanoic acid, ethanoic acid, propanoic acid, butanoic acid, pentanoic acid, hexanoic acid, heptanoic acid, octanoic acid, nonanoic acid, decanoic acid, undecanoic acid, dodecanoic acid, tridecanoic acid, tetradecanoic acid, pentadecanoic acid, hexadecanoic acid, heptadecanoic acid, octadecanoic acid, and nonadecanoic acid.

[0062] Examples of the unsaturated fatty acid include propenoic acid (acrylic acid), 2-methylprop-2-enoic acid (methacrylic acid), 2-butenoic acid, 3-butenoic acid, 4-pentenoic acid, 5-hexenoic acid, 6-heptenoic acid, 7-octenoic acid, 8-nonenoic acid, 9-decenoic acid, 10-undecenoic acid, 11-dodecenoic acid, 12-tridecenoic acid, 9-tetradecenoic acid, 13-tetradecenoic acid, 14-pentadecenoic acid, 9-hexadecenoic acid, 15-hexadecenoic acid, 16-heptadecenoic acid, 9-octadecenoic acid, 11-octadecenoic acid, 17-octadecenoic acid, and 18-nonadecenoic acid. unsaturated fatty acids having a carbon-carbon double bond such as propynoic acid, 3-butynoic acid, 4-pentynoic acid, 5-hexynoic acid, 6-heptynoic acid, 7-octynoic acid, 8-nonynoic acid, 9-decynoic acid, 10-undecynoic acid, 11-dodecynoic acid, 12-tridecynoic acid, 9-tetradecynoic acid, 13-tetradecynoic acid, 14-pentadecynoic acid, 9-hexadecynoic acid, 15-hexadecynoic acid, 16-heptadecynoic acid, 9-octadecynoic acid, 11-octadecynoic acid, 17-octadecynoic acid, and 18-nonadecynoic acid.

[0063] The fatty acid constituting the fatty acid metal salt is preferably an unsaturated fatty acid, more preferably an unsaturated fatty acid having a carbon-carbon double bond, further preferably an unsaturated fatty acid having 2 to 8 carbon atoms and a carbon-carbon double bond, and particularly preferably methacrylic acid or acrylic acid.

[0064] The fatty acid metal salt is preferably a divalent metal salt of an unsaturated fatty acid, more preferably a zinc salt of an unsaturated fatty acid, and particularly preferably zinc acrylate or zinc methacrylate.

[0065] In the present invention, it is particularly preferable to use zinc acrylate and / or zinc methacrylate as compound (3).

[0066] The cyclic complex of the present invention is produced by dissolving compound (3) in a solvent and crystallizing it. Examples of the solvent include chloroform, tetrahydrofuran (THF), acetone, methyl ethyl ketone, ethyl acetate, methyl propionate, dioxane, and a mixed solvent of at least one of these solvents with water. As the solvent, it is preferable to use chloroform or a mixed solution of tetrahydrofuran (THF) and water. Below, a production method using chloroform as the solvent and a production method using a THF / water mixed solvent as the solvent will be described.

[0067] In the production method using chloroform as a solvent, for example, compound (3) is dissolved in chloroform. After removing the insoluble matter, a non-polar solvent is added and the mixture is allowed to stand to precipitate crystals. It is also preferable to collect the precipitated crystals, wash them with water, and dry them.

[0068] The production method using chloroform as a solvent is preferably carried out under an inert atmosphere. Specifically, the step of removing insoluble matter and the step of precipitating crystals are preferably carried out under an inert atmosphere. Examples of the inert gas include nitrogen gas, argon gas, and helium gas.

[0069] The amount of chloroform to be added is not particularly limited, but is preferably 1 mL or more, more preferably 2 mL or more, and even more preferably 5 mL or more, and is preferably 200 mL or less, more preferably 100 mL or less, and even more preferably 50 mL or less, relative to 1 g of compound (3). If the amount of chloroform to be added is within the above range, the yield of the complex crystal is improved.

[0070] The method for removing the insoluble matter is not particularly limited, but examples thereof include filtration and centrifugation.

[0071] Examples of the non-polar solvent include hydrocarbon solvents such as hexane, toluene, cyclohexane, heptane, pentane, etc. Among these, hexane is particularly preferable from the viewpoint of improving the yield of the complex crystal.

[0072] The amount of the non-polar solvent to be added is not particularly limited, but is preferably 10 mL or more, more preferably 50 mL or more, even more preferably 100 mL or more, and is preferably 1000 mL or less, more preferably 500 mL or less, and even more preferably 200 mL or less, relative to 10 mL of chloroform. If the amount of the non-polar solvent to be added is within the above range, the yield of the complex crystal can be improved and the amount of work required for recovering the non-polar solvent can be reduced.

[0073] The time for which the non-polar solvent is added to the chloroform solution of compound (3) and left to stand is not particularly limited, but is preferably 24 hours or more, more preferably 48 hours or more, even more preferably 72 hours or more, more preferably 180 days or less, and even more preferably 100 days or less. If the time for which the compound is brought into contact with the non-polar solvent and left to stand is within the above range, the yield of the complex crystal can be improved and the working time can be saved.

[0074] The method for recovering the precipitated crystals is not particularly limited, and examples thereof include filtration.

[0075] The method for drying the recovered crystals is not particularly limited, and examples thereof include drying under reduced pressure, drying at normal pressure, etc. The drying temperature is not particularly limited, but is preferably 20°C to 90°C.

[0076] In the above-mentioned production method, the steps other than drying are preferably carried out at a temperature of 0° C. to 50° C., and more preferably at about room temperature (25° C.).

[0077] As a production method using a THF / water mixed solvent as a solvent, for example, compound (3) is placed in a THF / water mixed solvent, insoluble matter is removed, and then a concentrated solution (containing complex crystals) is obtained by evaporating THF. It is preferable to recover a precipitate (complex crystals) from the obtained concentrated solution, wash it with a small amount of water, and dry it.

[0078] The volume ratio of THF to water (THF / water) is preferably 0.1 or more, more preferably 1 or more, and even more preferably 10 or more, preferably 1000 or less, more preferably 100 or less, and even more preferably 50 or less. If the volume ratio of THF / water is within the above range, the yield of the complex crystal is improved.

[0079] The amount of the THF / water mixed solvent is not particularly limited, but is preferably 0.5 mL or more, more preferably 1 mL or more, even more preferably 2 mL or more, and preferably 100 mL or less, more preferably 80 mL or less, and even more preferably 50 mL or less, relative to 1 g of compound (3). If the amount of the THF / water mixed solvent added is within the above range, the yield of the complex crystal is improved.

[0080] The method for removing the insoluble matter is not particularly limited, but examples thereof include filtration and centrifugation.

[0081] The time for which the THF / water mixed solvent solution of compound (3) is allowed to stand in the air is not particularly limited, but it is preferable to allow the solution to stand until the liquid volume becomes 1 / 2 to 1 / 3 of the initial liquid volume, and more preferably until the liquid volume becomes 1 / 4 to 1 / 10 of the initial liquid volume. Complex crystals precipitate in the concentrated solution from which THF has evaporated. If the time for allowing the solution to stand is within the above range, the yield of the complex crystals can be improved and the working time can be saved.

[0082] The method for recovering the precipitate (complex crystals) from the obtained concentrated solution is not particularly limited, and examples thereof include filtration, etc. The method for drying the recovered crystals is not particularly limited, and examples thereof include drying under reduced pressure, drying under normal pressure, etc. The drying temperature is not particularly limited, and is preferably 20°C to 90°C.

[0083] In the above-mentioned production method, the steps other than drying are preferably carried out at a temperature of 0° C. to 50° C., and more preferably at about room temperature (25° C.).

[0084] The carbon-carbon unsaturated bond of the cyclic complex of the present invention reacts with a compound having an ethylenically unsaturated bond. Therefore, the cyclic complex of the present invention is useful as a co-crosslinking agent for rubber compositions, coating compositions, adhesive compositions, etc. The cyclic complex of the present invention can be suitably used as a co-crosslinking agent for rubber compositions.

[0085] The present invention includes a crystal of the cyclic complex. The crystal of the cyclic complex of the present invention is considered to be obtained by forming a cyclic structure using the solvent molecules as a template when compound (3) is dissolved in a solvent and crystallized. In the present invention, the solvent molecules are called template molecules, but it is not necessary to remove the template molecules from the obtained cyclic complex crystal, and it is preferable that the template molecules are incorporated into the cyclic complex crystal.

[0086] The crystal of the cyclic complex of the present invention preferably contains two template molecules (solvent molecules) per one molecule of the cyclic complex. The template molecule is not particularly limited as long as it is a solvent molecule that can be used to prepare a cyclic complex. The template molecule is preferably at least one selected from the group consisting of, for example, chloroform, acetone, methyl ethyl ketone, ethyl acetate, methyl propionate, and dioxane.

[0087] The crystal of the cyclic complex of the present invention has a repeating unit formed by stacking three layers of cyclic structures. FIG. 32 is an explanatory diagram showing the state in which the cyclic structures of the cyclic complex of the present invention are stacked. FIG. 33 is a plan view showing the state in which the cyclic structures of the cyclic complex of the present invention are stacked. The cyclic structures of the cyclic complex are stacked up and down while being shifted by a predetermined distance in the same horizontal direction, and three layers of cyclic structures form a repeating unit. In the drawing, the cyclic structure of the upper layer of the lower repeating unit is illustrated as the fourth layer. The upper layer of the lower repeating unit and the upper layer of the upper repeating unit are present at the same position in the horizontal direction. That is, in FIG. 32, the left end of the cyclic structure of the upper layer of the lower repeating unit and the left end of the cyclic structure of the upper layer of the upper repeating unit are aligned in the horizontal direction.

[0088] Figure 34 is an explanatory diagram showing an embodiment in which template molecules (solvent molecules: chloroform) are incorporated into a crystal of a cyclic complex. Three cyclic complexes and template molecules (solvent molecules: chloroform) exist on the same plane. The template molecules (solvent molecules: chloroform) used for crystallization exist in the gaps between the three cyclic complexes.

[0089] Figure 35 shows two molecules of the cyclic complex in Figure 34 (for example, the cyclic complex on the left and the cyclic complex on the bottom) observed from a perspective parallel to the paper, showing the position of the template molecule (solvent molecule) in a plane. The template molecule (solvent molecule: chloroform) is not in the center of the plane, but is slightly shifted up and down.

[0090] 36 is an explanatory diagram showing a state in which template molecules (solvent molecules: chloroform) are incorporated into a crystal of a cyclic complex, as viewed from the horizontal direction. Two template molecules (solvent molecules: chloroform) are present above and below the plane formed by one cyclic structure of the cyclic complex.

[0091] The present invention includes a rubber composition containing (a) a base rubber, (b) a co-crosslinking agent, and (c) a crosslinking initiator, wherein (b) the co-crosslinking agent contains the cyclic complex of the present invention. The present invention also includes a rubber composition containing (a) a base rubber, (b) a co-crosslinking agent, and (c) a crosslinking initiator, wherein (b) the co-crosslinking agent contains crystals of the cyclic complex of the present invention. Each component will be described below.

[0092] [(a) Base rubber] (a) Examples of the base rubber include butyl rubber, isoprene rubber, polybutadiene rubber, styrene butadiene rubber, natural rubber, nitrile rubber such as chloroprene rubber and acrylonitrile butadiene rubber, hydrogenated nitrile rubber, norbornene rubber, ethylene propylene rubber, ethylene-propylene-diene rubber, acrylic rubber, ethylene-acrylate rubber, fluororubber, chlorosulfonated polyethylene rubber, epichlorohydrin rubber, silicone rubber, urethane rubber, polysulfide rubber, phosphanzene rubber, and 1,2-polybutadiene. These may be used alone or in combination of two or more.

[0093] Among these, (a) the base rubber is preferably polybutadiene rubber, more preferably high-cis polybutadiene rubber. By using high-cis polybutadiene, the mechanical properties of the resulting cured rubber are improved. The high-cis polybutadiene rubber has cis-1,4-bonds in an amount of 40% by mass or more, preferably 80% by mass or more, more preferably 90% by mass or more, and even more preferably 95% by mass or more.

[0094] The content of high-cis polybutadiene in the base rubber is preferably at least 60 mass%, more preferably at least 80 mass%, and even more preferably at least 90 mass%. It is also preferable that the (a) base rubber consists solely of high-cis polybutadiene.

[0095] The high-cis polybutadiene preferably has a 1,2-vinyl bond content of 2.0 mass % or less, more preferably 1.7 mass % or less, and further preferably 1.5 mass % or less. If the 1,2-vinyl bond content is too high, the physical properties of the cured rubber may deteriorate.

[0096] The high-cis polybutadiene is preferably one synthesized using a rare earth element catalyst. In particular, the use of a neodymium-based catalyst using a neodymium compound, which is a lanthanum series rare earth element compound, is preferred because it can produce a polybutadiene rubber having a high content of 1,4-cis bonds and a low content of 1,2-vinyl bonds with excellent polymerization activity.

[0097] The high-cis polybutadiene preferably has a Mooney viscosity (ML1+4(100°C)) of 30 or more, more preferably 32 or more, even more preferably 35 or more, and preferably 140 or less, more preferably 120 or less, even more preferably 100 or less, and most preferably 55 or less. The Mooney viscosity (ML1+4(100°C)) in the present invention is a value measured in accordance with JIS K6300 using an L rotor under conditions of a preheating time of 1 minute, a rotor rotation time of 4 minutes, and a temperature of 100°C.

[0098] The high cis polybutadiene preferably has a molecular weight distribution Mw / Mn (Mw: weight average molecular weight, Mn: number average molecular weight) of 2.0 or more, more preferably 2.2 or more, even more preferably 2.4 or more, most preferably 2.6 or more, and preferably 6.0 or less, more preferably 5.0 or less, even more preferably 4.0 or less, and most preferably 3.0 or less. If the molecular weight distribution (Mw / Mn) of the high cis polybutadiene is too small, the workability may decrease, and if it is too large, the physical properties of the rubber cured product may decrease. The molecular weight distribution is measured by gel permeation chromatography (manufactured by Tosoh Corporation, "HLC-8120GPC") using a differential refractometer as a detector under the conditions of column: GMHHXL (manufactured by Tosoh Corporation), column temperature: 40°C, and mobile phase: tetrahydrofuran, and calculated as a standard polystyrene equivalent value.

[0099] [(b) Co-crosslinking agent] The rubber composition of the present invention contains the (b1) cyclic complex or crystals thereof of the present invention as a co-crosslinking agent. The content of the (b1) cyclic complex or crystals thereof in the rubber composition is preferably 5 parts by mass or more, more preferably 10 parts by mass or more, even more preferably 15 parts by mass or more, and preferably 70 parts by mass or less, more preferably 60 parts by mass or less, and even more preferably 50 parts by mass or less, per 100 parts by mass of the base rubber. If the content of the (b1) cyclic complex or crystals thereof is within the above range, the mechanical properties of the obtained cured rubber product will be better.

[0100] The rubber composition of the present invention may contain, as a co-crosslinking agent, (b2) an α,β-unsaturated carboxylic acid having 3 to 8 carbon atoms and / or a metal salt thereof, in addition to the (b1) cyclic complex or a crystal thereof.

[0101] (b2) Examples of the α,β-unsaturated carboxylic acid having 3 to 8 carbon atoms include acrylic acid, methacrylic acid, fumaric acid, maleic acid, and crotonic acid.

[0102] (b2) Examples of the metal constituting the metal salt of the α,β-unsaturated carboxylic acid having 3 to 8 carbon atoms include monovalent metal ions such as sodium, potassium, and lithium; divalent metal ions such as magnesium, calcium, zinc, barium, and cadmium; trivalent metal ions such as aluminum; and other ions such as tin and zirconium. The metal components can be used alone or in a mixture of two or more kinds. Among these, divalent metals such as magnesium, calcium, zinc, barium, and cadmium are preferable as the metal components. This is because the use of a divalent metal salt of an α,β-unsaturated carboxylic acid having 3 to 8 carbon atoms makes it easier for metal crosslinks to form between rubber molecules. The α,β-unsaturated carboxylic acid having 3 to 8 carbon atoms and / or its metal salt may be used alone or in a combination of two or more kinds.

[0103] (b2) The α,β-unsaturated carboxylic acid having 3 to 8 carbon atoms and / or its metal salt is preferably acrylic acid, methacrylic acid, zinc acrylate, or zinc methacrylate.

[0104] The amount of the (b2) α,β-unsaturated carboxylic acid having 3 to 8 carbon atoms and / or its metal salt is preferably at least 1 part by mass, more preferably at least 5 parts by mass, and even more preferably at least 10 parts by mass, and is preferably at most 50 parts by mass, more preferably at most 40 parts by mass, and even more preferably at most 30 parts by mass, per 100 parts by mass of the (a) base rubber.

[0105] The content of the (b2) α,β-unsaturated carboxylic acid having 3 to 8 carbon atoms and / or a metal salt thereof in the rubber composition of the present invention is preferably lower than the content of the (b1) cyclic complex or a crystal thereof.

[0106] (c) The crosslinking initiator is blended to crosslink the (a) base rubber component. (c) The crosslinking initiator is not particularly limited, and examples thereof include sulfur, organic peroxides, and triazine derivatives, which may be used alone or in combination of two or more kinds.

[0107] Examples of sulfur used as a crosslinking initiator include powdered sulfur, precipitated sulfur, colloidal sulfur, insoluble sulfur, highly dispersible sulfur, soluble sulfur, etc. Commercially available products include those from Tsurumi Chemical Industry Co., Ltd., Karuizawa Sulfur Co., Ltd., Shikoku Chemical Industry Co., Ltd., Flexis, Nippon Kanzuri Kogyo Co., Ltd., Hosoi Chemical Industry Co., Ltd., etc. These may be used alone or in combination of two or more kinds.

[0108] Specific examples of the organic peroxide include dialkyl peroxide, peroxy ester, peroxy ketal, and hydroperoxide. Examples of the dialkyl peroxide include di(2-t-butylperoxyisopropyl)benzene, dicumyl peroxide, 2,5-dimethyl-2,5-di(t-butylperoxy)hexane, t-butylcumyl peroxy, di-t-hexyl peroxy, di-t-butyl peroxy, and 2,5-dimethyl-2,5-di(t-butylperoxy)hexyne-3. Examples of the peroxy ester include t-butyl peroxy maleate, t-butyl peroxy-3,3,5-trimethylcyclohexanoate, t-butyl peroxy laurate, t-butyl peroxy isopropyl monocarbonate, t-hexyl peroxy benzoate, 2,5-dimethyl-2,5-di(benzoylperoxy)hexane, t-butyl peroxy acetate, and t-butyl peroxy benzoate. Examples of peroxyketals include 1,1-di(t-hexylperoxy)-3,3,5-trimethylcyclohexane, 1,1-di(t-hexylperoxy)cyclohexane, 1,1-di(t-butylperoxy)-2-methylcyclohexane, 1,1-di(t-butylperoxy)cyclohexane, 2,2-di(t-butylperoxy)butane, n-butyl-4,4-di(t-butylperoxy)valerate, and 2,2-di(4,4-di(t-butylperoxy)cyclohexyl)propane. Examples of hydroperoxides include p-menthane hydroperoxide and diisopropylbenzene hydroperoxide. These organic peroxides may be used alone or in combination of two or more.

[0109] As the (c) crosslinking initiator used in the rubber composition of the present invention, an organic peroxide is suitable. Specific examples of the organic peroxide include dicumyl peroxide, 1,1-bis(t-butylperoxy)-3,3,5-trimethylcyclohexane, 2,5-dimethyl-2,5-di(t-butylperoxy)hexane, and di-t-butyl peroxide. Among these, dicumyl peroxide is preferably used.

[0110] The content of the (c) crosslinking initiator is preferably 0.2 parts by mass or more, more preferably 0.4 parts by mass or more, and even more preferably 0.6 parts by mass or more, and is preferably 5.5 parts by mass or less, more preferably 5.0 parts by mass or less, and even more preferably 4.5 parts by mass or less, based on 100 parts by mass of the base rubber. If the content of the (c) crosslinking initiator is within the above range, the curing reaction of the rubber composition will be good.

[0111] [(d) Filler] The rubber composition of the present invention may contain a filler. Examples of the filler include inorganic fillers such as silica, carbon black, zinc oxide, barium sulfate, calcium carbonate, magnesium oxide, tungsten powder, molybdenum powder, aluminum hydroxide, alumina (aluminum oxide), clay, talc, and mica. Zinc oxide is particularly preferred as the filler. Zinc oxide is thought to function as a vulcanization aid and increase the hardness of the cured product.

[0112] The silica is not particularly limited, and for example, silica prepared by a dry method (anhydrous silica) or silica prepared by a wet method (hydrated silica) can be used. Among them, hydrated silica prepared by a wet method is preferable because it has a large number of silanol groups. As the silica, for example, those manufactured and sold by Evonik Degussa, Solvay, Tosoh Silica Co., Ltd., Tokuyama Corporation, etc. can be used. These silicas may be used alone or in combination of two or more.

[0113] The silica is preferably used in combination with a silane coupling agent. Examples of the silane coupling agent include sulfide-based silane coupling agents such as bis(3-triethoxysilylpropyl) disulfide and bis(3-triethoxysilylpropyl) tetrasulfide; mercapto-based silane coupling agents such as 3-mercaptopropyltrimethoxysilane, NXT-Z100, NXT-Z45, and NXT manufactured by Momentive; vinyl-based silane coupling agents such as vinyltriethoxysilane and vinyltrimethoxysilane; 3-aminopropyltriethoxysilane and 3-aminopropyltriethoxysilane; Examples of the silane coupling agents include amino-based silane coupling agents such as methoxysilane and 3-(2-aminoethyl)aminopropyltriethoxysilane; glycidoxy-based silane coupling agents such as γ-glycidoxypropyltriethoxysilane and γ-glycidoxypropyltrimethoxysilane; nitro-based silane coupling agents such as 3-nitropropyltrimethoxysilane and 3-nitropropyltriethoxysilane; chloro-based silane coupling agents such as 3-chloropropyltrimethoxysilane and 3-chloropropyltriethoxysilane; etc. These silane coupling agents may be used alone or in combination of two or more.

[0114] When containing silane coupling agent, the content of silane coupling agent is preferably 1 part by mass or more, more preferably 3 parts by mass or more, even more preferably 5 parts by mass or more, and particularly preferably 8 parts by mass or more, based on 100 parts by mass of silica. Also, the content of the silane coupling agent is preferably 25 parts by mass or less, more preferably 20 parts by mass or less, and even more preferably 15 parts by mass or less, based on 100 parts by mass of silica.

[0115] Examples of the clay include calcined clay and kaolin clay. Specific examples of the clay include SILLITIN (registered trademark) Z manufactured by HOFFMANN MINERAL, SATINTONE (registered trademark) W manufactured by ENGELHARD, NN kaolin clay manufactured by Tsuchiya Kaolin Kogyo Co., Ltd., and PoleStar 200R manufactured by Imerys Specialties Japan.

[0116] Specific examples of the talc include Hitron A manufactured by Takehara Chemical Industry Co., Ltd., MICRO ACE (registered trademark) K-1 manufactured by Nippon Talc Co., Ltd., and Mistron (registered trademark) Vapor manufactured by Imerys Specialties Japan.

[0117] Carbon black may be any of those commonly used in the rubber industry, such as N134, N110, N220, N234, N219, N339, N330, N326, N351, N550, and N762. Commercially available products include those from Asahi Carbon Co., Ltd., Cabot Japan Co., Ltd., Tokai Carbon Co., Ltd., Mitsubishi Chemical Corporation, Lion Corporation, Shin-Nichika Carbon Co., Ltd., Columbia Carbon Co., Ltd., and the like. These may be used alone or in combination of two or more.

[0118] The amount of the filler is preferably at least 1 part by mass, more preferably at least 3 parts by mass, and even more preferably at least 5 parts by mass, and is preferably at most 50 parts by mass, more preferably at most 20 parts by mass, and even more preferably at most 10 parts by mass, per 100 parts by mass of the (a) base rubber. If the amount of the filler is within the above range, it becomes easier to balance the weight adjustment and the mechanical properties.

[0119] The rubber composition may contain a vulcanization accelerator. Examples of the vulcanization accelerator include thiazole-based vulcanization accelerators such as 2-mercaptobenzothiazole and di-2-benzothiazolyl disulfide; dithiocarbamate-based accelerators such as zinc dimethyldithiocarbamate; thiuram-based vulcanization accelerators such as tetramethylthiuram disulfide (TMTD), tetrabenzylthiuram disulfide (TBzTD), and tetrakis(2-ethylhexyl)thiuram disulfide (TOT-N); sulfenamide-based vulcanization accelerators such as N-cyclohexyl-2-benzothiazylsulfenamide (CBS), N-tert-butyl-2-benzothiazolylsulfenamide (TBBS), N-oxyethylene-2-benzothiazolesulfenamide, and N,N'-diisopropyl-2-benzothiazolesulfenamide; and guanidine-based vulcanization accelerators such as diphenylguanidine, di-orthotolylguanidine, and orthotolylbiguanidine. As commercially available products, products from Sumitomo Chemical Co., Ltd., Ouchi Shinko Chemical Industry Co., Ltd., etc. can be used. These may be used alone or in combination of two or more kinds.

[0120] The rubber composition may contain additives such as pigments, oils, waxes, peptizers, softeners, and antioxidants, as required.

[0121] Examples of the oil include process oil, vegetable oil, and mixtures thereof. Examples of the process oil include paraffin-based process oil, aromatic process oil, naphthenic process oil, and the like. Examples of the vegetable oil include castor oil, cottonseed oil, linseed oil, rapeseed oil, soybean oil, palm oil, coconut oil, peanut oil, rosin, pine oil, pine tar, tall oil, corn oil, rice oil, safflower oil, sesame oil, olive oil, sunflower oil, palm kernel oil, camellia oil, jojoba oil, macadamia nut oil, and tung oil. These may be used alone or in combination of two or more.

[0122] The wax is not particularly limited, and examples thereof include petroleum waxes such as paraffin wax and microcrystalline wax, natural waxes such as vegetable wax and animal wax, synthetic waxes such as polymers of ethylene, propylene, etc. These may be used alone or in combination of two or more.

[0123] Examples of the antioxidant include naphthylamine-based antioxidants such as phenyl-α-naphthylamine; diphenylamine-based antioxidants such as octylated diphenylamine and 4,4'-bis(α,α'-dimethylbenzyl)diphenylamine; N-isopropyl-N'-phenyl-p-phenylenediamine, N-(1,3-dimethylbutyl)-N'-phenyl-p-phenylenediamine, and N,N'-di-2-naphthyl-p-phenylenediamine. Examples of the antioxidants include p-phenylenediamine antioxidants such as p-phenylenediamine, quinoline antioxidants such as polymers of 2,2,4-trimethyl-1,2-dihydroquinoline, monophenol antioxidants such as 2,6-di-t-butyl-4-methylphenol and styrenated phenol, and bis-, tris-, and polyphenol antioxidants such as tetrakis-[methylene-3-(3',5'-di-t-butyl-4'-hydroxyphenyl)propionate]methane. These antioxidants may be used alone or in combination of two or more.

[0124] The content of the peptizing agent is preferably 0.1 part by mass or more and 5 parts by mass or less per 100 parts by mass of the (a) base rubber.

[0125] The rubber composition is obtained by mixing and kneading (a) base rubber, (b) co-crosslinking agent, (c) crosslinking initiator, and other components as necessary. The kneading method is not particularly limited, and may be performed using a known kneading machine such as a kneading roll, a Banbury mixer, or a kneader.

[0126] The cured product of the rubber composition of the present invention is obtained by curing the kneaded rubber composition, and is preferably molded, for example, by a hot press. The molding temperature is preferably 120° C. or higher, more preferably 150° C. or higher, even more preferably 160° C. or higher, and preferably 170° C. or lower. The molding pressure is preferably 2.9 MPa to 11.8 MPa. The molding time is preferably 10 minutes to 60 minutes.

[0127] The present invention includes a cured product (crosslinked rubber) of the rubber composition. EXAMPLES

[0128] The present invention will be described in detail below with reference to examples. However, the present invention is not limited to the following examples, and all modifications and embodiments that do not deviate from the spirit of the present invention are included within the scope of the present invention.

[0129] [Evaluation method] (1) ESI-MS spectrum The ESI-MS spectrum was measured using the following equipment. Equipment: JEOL JMS-T100LP AccuTOF LC-plus

[0130] (2) 1 H-NMR spectrum Using the following equipment, 1 H-NMR spectrum was measured. Equipment: Bruker Ascend 500

[0131] (3) 13 C-NMR spectrum Using the following equipment, 13 C-NMR spectrum was measured. Equipment: Bruker Ascend 500

[0132] (4) Powder X-ray diffraction spectrum The powder X-ray diffraction spectrum was measured using a wide-angle X-ray diffractometer (Rigaku Corporation, "RINT-TTR III type"). The measurement sample was pulverized using an agate mortar. The measurement conditions were as follows: X-ray source; CuKα ray Tube voltage-tube current: 50kV-300mA Step width; 0.02deg. Measurement speed; 5deg. / min Slit system; divergence-reception-scattering: 0.5deg.-open-0.5deg. Monochromator; Diffraction curved crystal monochromator

[0133] (5)X-ray crystal structure analysis The X-ray diffraction of the single crystal was measured using a Rigaku "XtaLABACF10 (RCD3)" diffractometer. X-ray source; CuKα ray Detector: Hypix

[0134] (6) Scanning Electron Microscope (SEM) Pretreatment conditions Device name: Microtome EM UC7 (Leica Microsystems) Temperature: -120℃ Vapor deposition conditions: Os 1nm setting Observation conditions Device name: Teneo (Thermofisher) Acceleration voltage: 15 kV Current amount: 1.6nA Detection mode: T1 (backscattered electrons)

[0135] (7) Scanning Transmission Electron Microscope (STEM) / Transmission Electron Microscope (TEM) Pretreatment conditions Device name: Microtome EM UC7 (Leica Microsystems) Temperature: -120℃ Thickness: 50nm, 100nm setting STEM-EDS observation Equipment name: JEM-F200 (Jeol Ltd) Detector: ADF, SDD Accelerating voltage: 200 kV Camera length: 300mm WD: 3.2mm

[0136] (8) Slab hardness The rubber composition was press-molded at 170°C for 20 minutes to produce a sheet with a thickness of about 2 mm, which was then stored at 23°C for two weeks. The sheets were stacked in three or more layers to avoid the influence of the measurement substrate, and the hardness was measured using an automatic hardness tester (Digitest II, manufactured by H. Burleith Co., Ltd.). A Shore C detector was used.

[0137] (9) Dynamic viscoelasticity The rubber composition was press-molded at 170° C. for 20 minutes to produce a sheet having a thickness of about 0.5 mm. A sample piece having a width of 4 mm and a clamp distance of 20 mm was cut out from this sheet, and the storage modulus E′ was measured under the following conditions. Equipment: Dynamic viscoelasticity measuring device "Rheogel-E4000" manufactured by UBM Measurement mode: Tensile Measurement temperature: 20℃ Excitation frequency: 10Hz Measured strain: 200%

[0138] (10) Network chain density (mmol / cm 3 ) The network chain density of the cured rubber was calculated from the swelling measurement of a slab sample of the cured rubber. The rubber composition was kneaded with a kneading roll and heat-treated at 170°C for 30 minutes to prepare a slab with a thickness of 0.5 mm, a length of 12 cm, and a width of 14 cm. A slab with a thickness of 0.5 mm and a size of 2 cm x 2 cm was cut out from this slab to prepare a slab sample for measurement.

[0139] The swelling measurement was carried out by immersing the obtained slab sample in toluene (molecular weight: 92 mol / g) for 24 hours at 40° C. The mass of the slab (23° C.) before and after swelling was measured, and the effective crosslink density was calculated using the Flory-Rehner equation.

[0140]

number

[0141]

number

[0142] (11) Tensile test The tensile test of the cured rubber was performed according to JIS K6254 (2016). Specifically, the rubber composition was kneaded with a kneading roll and heat-treated at 170°C for 20 minutes to produce a slab with a thickness of approximately 0.5 mm. Two test pieces were punched out from this slab and stored at 23°C for two weeks. The shape of the test piece was a rectangular No. 4 shape (width 15 mm, total length 100 mm, thickness 0.5 mm, gauge length 20 mm). A tensile test was performed using a precision universal testing machine (Shimadzu Corporation, AUTOGRAPH (registered trademark) AG-X plus) to create a stress-strain curve. The test temperature was 23°C, the gripper interval was 60 mm, and the gripper movement speed was 50 mm / min.

[0143] (Manufacturing Example 1) Under an argon atmosphere, zinc methacrylate (207 mg, 0.88 mmol) was placed in 2 ml of chloroform, the insoluble matter was removed by filtration, and the mixture was transferred to a microtube that was placed inside a Schlenk tube. In addition, 10 ml of hexane was added to the Schlenk tube outside the microtube, and the mixture was left to stand for one day to precipitate a complex crystal. A single crystal was sampled from the precipitate, and X-ray structural analysis was performed.

[0144] (Manufacturing Example 2) Zinc methacrylate (4.715 g, 20 mmol) was added to 70 ml of a THF / water mixed solvent (THF / water = 10 / 1 (volume ratio)). The resulting zinc methacrylate-containing liquid was centrifuged, and the supernatant was transferred to a test tube. The supernatant (50 mL) was left to stand in the air until the liquid volume was reduced to about 10 mL, and the THF was evaporated to obtain a concentrated liquid. The precipitate was collected from the obtained concentrated liquid by filtration, washed with a small amount of water, and dried under vacuum at room temperature to obtain a complex crystal (2.726 g, yield 58%).

[0145] (Comparative Manufacturing Example 1) Zinc methacrylate (10 mmol, 2.35 g) was dissolved in approximately 100 mL of water, and the insoluble matter was filtered off. The mixture was left to stand on a hot plate at 40°C for 3 days, and the water was evaporated until only a few mL of water remained. Plate-like crystals were collected by filtration and washed with water to obtain 1.7 g of crystals. X-ray crystal structure analysis of the obtained crystals was performed.

[0146] The structures of the complex crystals obtained in the above-mentioned Example Production Examples 1 and 2 were determined by single crystal X-ray structure analysis. As a result, it was found that the complex obtained in Example Production Example 1 had the cyclic structure shown in FIG. 10, and the complex obtained in Example Production Example 2 had the cyclic structure shown in FIG. 6.

[0147] The cyclic complex shown in Figure 6 is formed by bonding six structural units represented by formula (1), and in the center of the complex in plan view, there is THF, the solvent used in the synthesis of the cyclic complex. The crystal of the cyclic complex shown in Figure 6 is C 96 H 120 O 48 Zinc 12 It has the molecular formula 2(C4H8O). The cyclic complex shown in Figure 10 is formed by bonding six structural units represented by formula (1), and in the center of the complex in plan view is the chloroform solvent used in the synthesis of the cyclic complex. 96 H 120 O 48 Zinc 12 It is represented by the molecular formula 2(CHCl3).

[0148] For commercially available zinc methacrylate crystals (product name: manufactured by Aldrich), the results of determining the structure by single crystal X-ray structure analysis of the crystals obtained in Comparative Production Example 1 and the X-ray diffraction peak pattern predicted from the results are shown in Figures 7 and 11, respectively. Since Figure 11 coincides with Figure 5, it was found that the commercially available zinc methacrylate crystals have a linear structure.

[0149] From the above results, it is apparent that the complex crystals obtained in Examples 1 and 2 are compounds represented by formula (2) (in formula (2), M 1 , M 2 is zinc, R 1 ~R 4 It was confirmed that the structural formula was -C(CH3)=CH2, and n was 6. Specifically, the complex crystals obtained in Production Examples 1 and 2 were compounds represented by the following structural formula (4).

[0150] [ka]

[0151] Furthermore, the complex crystal obtained in the above-mentioned Example 2 was subjected to mass spectrometry (ESI-MS) and nuclear magnetic resonance spectrometry ( 1 H-NMR, 13 C-NMR and powder X-ray diffraction analyses were carried out.

[0152] The ESI-MS spectrum of the complex crystal obtained in Example 2 is shown in Figure 1. In the spectrum shown in Figure 1, m / z = 450.80 is considered to correspond to Zn2(OOC-C(CH3)=CH2)4, which is the basic structural unit of the complex.

[0153] The complex crystals obtained in Example 2 1 The H-NMR spectrum is shown in Figure 2. 13 The C-NMR spectra are shown in Figure 3. In these spectra, the metal salts of methacrylic acid, while the acrylates in the complexes are in a relatively close environment, 13 The peak shape of the carbonyl carbon in C-NMR suggests that the environment is not completely single.

[0154] The X-ray diffraction spectrum of the complex crystal obtained in Example 2 is shown in Figure 4. The results of measuring the X-ray diffraction spectrum of commercially available zinc methacrylate crystals are shown in Figure 5. From these X-ray diffraction spectra, it was confirmed that the zinc methacrylate cyclic complex crystal obtained in Example 2 has a different crystal structure from commercially available zinc methacrylate crystals.

[0155] (Manufacturing Example 3) Zinc methacrylate (84.9 mmol, 20 g) was dissolved in 500 mL of acetone, and the insoluble matter was filtered off. The liquid was concentrated until the volume was about 1 / 5, and the precipitated solid was collected by filtration and dried to obtain 7 g of crystals. Powder X-ray diffraction of the obtained crystals was measured. Peaks were confirmed at 2θ=8.5°, 9.9°, 11.8°, and 13.0°, and it was determined that the crystals had the same cyclic structure as the crystals obtained in Example 1 and 2.

[0156] (Manufacturing Example 4) The same procedure was carried out by replacing the acetone in Example 3 with methyl ethyl ketone, and 6 g of crystals were obtained. The powder X-ray diffraction of the obtained crystals was measured. Since peaks were confirmed at 2θ=8.5°, 9.9°, 11.8°, and 13.0°, it was determined that the crystals had the same cyclic structure as the crystals obtained in Example 1 and 2.

[0157] (Manufacturing Example 5) The same procedure was carried out by replacing the acetone in Example 3 with ethyl acetate, and 7 g of crystals were obtained. The powder X-ray diffraction of the obtained crystals was measured. Since peaks were confirmed at 2θ=8.5°, 9.9°, 11.8°, and 13.0°, it was determined that the crystals had the same cyclic structure as the crystals obtained in Example 1 and 2.

[0158] (Example 6) The same procedure was carried out by replacing the acetone in Example 3 with methyl propionate, and 8 g of crystals were obtained. The powder X-ray diffraction of the obtained crystals was measured. Since peaks were confirmed at 2θ=8.5°, 9.9°, 11.8°, and 13.0°, it was determined that the crystals had the same cyclic structure as the crystals obtained in Example 1 and 2.

[0159] (Manufacturing Example 7) The same procedure was carried out by replacing the acetone in Example 3 with 1,4-dioxane, to obtain 8 g of crystals. Powder X-ray diffraction of the obtained crystals was measured. Peaks were confirmed at 2θ=8.5°, 9.9°, 11.8°, and 13.0°, and it was determined that the crystals had the same cyclic structure as the crystals obtained in Example 1 and 2.

[0160] (Comparative Manufacturing Example 2) Zinc methacrylate (84.9 mmol, 20 g) was dissolved in 500 mL of ethanol, and the insoluble matter was filtered off. The liquid was concentrated until the volume was about 1 / 5, and the precipitated solid was collected by filtration and dried to obtain 7 g of crystals. Powder X-ray diffraction of the crystals obtained was measured. Peaks were confirmed at 2θ = 9.9° and 11°, and it was determined that the crystal structure was linear zinc methacrylate.

[0161] (Comparative Manufacturing Example 3) The same procedure as in Comparative Production Example 2 was repeated except that ethanol was replaced with 2-propanol, and 4 g of crystals were obtained. Powder X-ray diffraction of the obtained crystals was measured. No peaks characteristic of linear or cyclic zinc methacrylate were observed, and it was determined that these crystal structures were not included.

[0162] (Comparative Manufacturing Example 4) The same procedure was carried out, except that ethanol in Comparative Production Example 2 was replaced with propyl acetate, to obtain 7 g of crystals. Powder X-ray diffraction of the obtained crystals was measured. In addition to an unknown peak, peaks were confirmed at 2θ = 9.9 ° and 11 °, so it was determined that the crystals contained crystals having a linear zinc methacrylate crystal structure.

[0163] (Comparative Manufacturing Example 5) The same procedure as in Comparative Production Example 2 was repeated except that ethanol was replaced with diisopropyl ether to obtain 2 g of crystals. Powder X-ray diffraction of the obtained crystals was measured. No peaks characteristic of linear or cyclic zinc methacrylate were observed, and it was determined that these crystal structures were not included.

[0164] (Comparative Manufacturing Example 6) The same procedure as in Comparative Production Example 2 was repeated except that acetonitrile was used instead of ethanol, and 4 g of crystals were obtained. Powder X-ray diffraction of the obtained crystals was measured. No peaks characteristic of linear or cyclic zinc methacrylate were observed, and it was determined that these crystal structures were not included.

[0165] (Comparative Manufacturing Example 7) The same procedure as in Comparative Production Example 2 was repeated except that ethanol was replaced with toluene, and 3 g of crystals were obtained. Powder X-ray diffraction of the obtained crystals was measured. No peaks characteristic of linear or cyclic zinc methacrylate were observed, and it was determined that these crystal structures were not included.

[0166] (Comparative Manufacturing Example 8) The same procedure was carried out by replacing the ethanol in Comparative Production Example 2 with cyclohexane, and 0.2 g of crystals was obtained. The powder X-ray diffraction of the obtained crystals was measured. In addition to an unknown peak, peaks were confirmed at 2θ=9.9° and 11°, so it was determined that the crystal structure was the same as that of linear zinc methacrylate.

[0167] [Preparation of Rubber Composition] According to the formulation shown in Tables 1 and 2, (a) base rubber, (b) co-crosslinking agent, and (d) zinc oxide were kneaded, and then (c) crosslinking initiator was added and kneaded to prepare a rubber composition. The material temperature during kneading of the rubber composition was 100°C to 130°C.

[0168] [Table 1]

[0169] [Table 2]

[0170] The materials used in Tables 1 and 2 are as follows: Polybutadiene rubber: JSR Corporation, "BR730" Zinc methacrylate: Sanshin Chemical Industry Co., Ltd., "Sunester SK-30" Zinc methacrylate cyclic complex: cyclic complex obtained in Example 2 Zinc oxide: "Ginrei R" manufactured by Toho Zinc Co., Ltd. Dicumyl peroxide: NOF Corporation, "Percumyl (registered trademark) D"

[0171] Table 1 shows the network chain density, storage modulus and hardness of the cured rubber (slab) produced from the rubber composition. Fig. 8 shows the results of comparing the stress-strain curves of the cured rubber produced from rubber composition No. 1 with those of the cured rubber produced from rubber composition No. 3, and Fig. 9 shows the results of comparing the stress-strain curves of the cured rubber produced from rubber composition No. 2 with those of the cured rubber produced from rubber composition No. 4. These results show that the cured rubber (crosslinked rubber) produced using the cyclic complex of the present invention is harder and has a higher tensile stress at the same strain than the cured rubber (crosslinked rubber) produced using the same amount of a commercially available co-crosslinking agent.

[0172] Table 2 shows the network chain density and hardness of the cured rubber (slab) produced from the rubber composition. Figures 24 to 31 show SEM and STEM photographs of the cured rubber produced from rubber compositions No. 5 to 8. These results show that the cured rubber (crosslinked rubber) using the cyclic complex or crystals of the present invention is more susceptible to microscale aggregation than the cured rubber (crosslinked rubber) using the same amount of a commercially available co-crosslinking agent, but there is no difference in nanoscale aggregation. [Industrial Applicability]

[0173] The cyclic complex or crystal of the present invention is useful as a co-crosslinking agent utilizing the reaction of carbon-carbon unsaturated bonds. It is particularly suitable as a co-crosslinking agent for rubber compositions. A rubber composition using the cyclic complex or crystal of the present invention as a co-crosslinking agent gives a hard cured product having a large tensile stress.

[0174] The rubber composition of the present invention can be used for sporting goods such as golf balls, tennis balls, and grips; industrial goods such as hoses, belts, and mats; medical goods such as syringe stoppers, syringe caps, and rubber stoppers for vials; shoe soles, tires, resin additives, anti-vibration rubber, and fenders.

[0175] A preferred embodiment (1) of the present invention is a cyclic complex characterized in that it has a structural unit represented by formula (1) as a structural unit constituting a cyclic structure.

[0176] [ka] [In formula (1), M 1 and M. 2 are the same or different metal atoms, and R 1 ~R 4 are the same or different and each represents a hydrogen atom, an alkyl group having 1 to 18 carbon atoms, an alkenyl group having 2 to 18 carbon atoms, or an alkynyl group having 2 to 18 carbon atoms. R 1 ~R 4At least one of these is an alkenyl group having 2 to 18 carbon atoms or an alkynyl group having 2 to 18 carbon atoms.]

[0177] A preferred embodiment (2) of the present invention is the cyclic complex according to embodiment (1) represented by formula (2).

[0178] [ka] [In formula (2), M 1 and M. 2 are the same or different metal atoms, and R 1 ~R 4 are the same or different and each represents a hydrogen atom, an alkyl group having 1 to 18 carbon atoms, an alkenyl group having 2 to 18 carbon atoms, or an alkynyl group having 2 to 18 carbon atoms. R 1 ~R 4 At least one of the groups is an alkenyl group having 2 to 18 carbon atoms or an alkynyl group having 2 to 18 carbon atoms. n is an integer of 3 or more.]

[0179] A preferred embodiment (3) of the present invention is 1 and M. 2 is a cyclic complex of embodiment (1) or (2) in which the metal atom has an oxidation number of +2.

[0180] A preferred embodiment (4) of the present invention is 1 and M. 2 is a cyclic complex of embodiment (1) or (2), in which at least one metal atom is selected from the group consisting of zinc, beryllium, lead, magnesium, nickel, and copper.

[0181] A preferred embodiment (5) of the present invention is R 1 ~R 4 is a cyclic complex according to any one of embodiments (1) to (4), in which R is an alkenyl group having 2 to 8 carbon atoms or an alkynyl group having 2 to 8 carbon atoms.

[0182] A preferred embodiment (6) of the present invention is R 1 ~R 4is a cyclic complex according to any one of embodiments (1) to (5), which is -CH=CH2 or -C(CH3)=CH2.

[0183] A preferred embodiment (7) of the present invention is R 1 ~R 4 is -CH=CH2 or -C(CH3)=CH2, M 1 and M. 2 is a cyclic complex according to any one of embodiments (1) to (6), in which the ring structure is zinc.

[0184] A preferred embodiment (8) of the present invention is a cyclic complex according to any one of embodiments (2) to (7), in which n is an integer of 10 or less.

[0185] A preferred embodiment (9) of the present invention is a crystal of a cyclic complex according to any one of the embodiments (1) to (8).

[0186] A preferred embodiment (10) of the present invention is a crystal of the cyclic complex of embodiment (9) which contains two molecules of template molecule per molecule of the cyclic complex.

[0187] A preferred embodiment (11) of the present invention relates to a crystal of the cyclic complex according to embodiment (10), wherein the template molecule is at least one selected from the group consisting of chloroform, acetone, methyl ethyl ketone, ethyl acetate, methyl propionate, and dioxane.

[0188] A preferred embodiment (12) of the present invention is a rubber composition comprising (a) a base rubber, (b) a co-crosslinking agent, and (c) a crosslinking agent, wherein (b) the co-crosslinking agent contains a cyclic complex according to any one of embodiments (1) to (8).

[0189] A preferred embodiment (13) of the present invention is a cured product of the rubber composition of embodiment (12).

[0190] A preferred embodiment (14) of the present invention is a rubber composition comprising (a) a base rubber, (b) a co-crosslinking agent, and (c) a crosslinking agent, wherein (b) the co-crosslinking agent contains a crystal of a cyclic complex according to any one of embodiments (9) to (11).

[0191] A preferred embodiment (15) of the present invention is a cured product of the rubber composition of embodiment (14).

Claims

1. A cyclic complex having a cyclic structure constituted by a structural unit represented by formula (1): 【Chemistry 1】 [In formula (1), M 1 and M. 2 are the same or different metal atoms, R 1 ~R 4 are the same or different and each represents a hydrogen atom, an alkyl group having 1 to 18 carbon atoms, an alkenyl group having 2 to 18 carbon atoms, or an alkynyl group having 2 to 18 carbon atoms. 1 ~R 4 At least one of these is an alkenyl group having 2 to 18 carbon atoms or an alkynyl group having 2 to 18 carbon atoms.]

2. The cyclic complex according to claim 1, represented by formula (2): 【Chemistry 2】 [In formula (2), M 1 and M. 2 are the same or different metal atoms, R 1 ~R 4 are the same or different and each represents a hydrogen atom, an alkyl group having 1 to 18 carbon atoms, an alkenyl group having 2 to 18 carbon atoms, or an alkynyl group having 2 to 18 carbon atoms. 1 ~R 4 At least one of the groups is an alkenyl group having 2 to 18 carbon atoms or an alkynyl group having 2 to 18 carbon atoms. n is an integer of 3 or more.

3. M 1 and M. 2 The cyclic complex according to claim 2 , wherein is a metal atom having an oxidation number of +2.

4. M 1 and M. 2 3. The cyclic complex according to claim 2, wherein is at least one metal atom selected from the group consisting of zinc, beryllium, lead, magnesium, nickel and copper.

5. R 1 ~R 4 The cyclic complex according to claim 2, wherein is an alkenyl group having 2 to 8 carbon atoms or an alkynyl group having 2 to 8 carbon atoms.

6. R 1 ~R 4 is -CH=CH 2 or -C(CH 3 ) = CH 2 The cyclic complex according to claim 2, wherein

7. R 1 ~R 4 is -CH=CH 2 or -C(CH 3 ) = CH 2 And M 1 and M. 2 The cyclic complex according to claim 2, wherein is zinc.

8. 3. The cyclic complex according to claim 2, wherein n is an integer of 10 or less.

9. A crystal of the cyclic complex according to any one of claims 1 to 8.

10. The crystal of the cyclic complex according to claim 9, which contains two molecules of the template molecule per molecule of the cyclic complex.

11. 11. The crystal of a cyclic complex according to claim 10, wherein the template molecule is at least one selected from the group consisting of chloroform, acetone, methyl ethyl ketone, ethyl acetate, methyl propionate, and dioxane.

12. A rubber composition comprising (a) a base rubber, (b) a co-crosslinking agent, and (c) a crosslinking agent, wherein (b) the co-crosslinking agent contains the cyclic complex according to any one of claims 1 to 8.

13. A cured product of the rubber composition according to claim 12.

14. A rubber composition comprising (a) a base rubber, (b) a co-crosslinking agent, and (c) a crosslinking agent, wherein (b) the co-crosslinking agent contains a crystal of the cyclic complex according to any one of claims 9 to 11.

15. A cured product of the rubber composition according to claim 14.

Citation Information

Patent Citations

  • Complex and process for preparing complex

    JP2018104306A

  • Complex and process for preparing complex

    JP2018104405A

  • Complex and manufacturing method of complex

    JP2020002020A

  • Complex and manufacturing method of complex

    JP2020002021A